Migraine and other headaches - Young, William B. (William Boyd), 1959- (AAN Press quality of life guide., 2004)
Headache is the most common complaint for which people see neurologists and the seventh most common reason they visit their primary care doctors. It is the third most common cause of missed work, and can seriously undermine the quality of life if not effectively managed. Migraine and Other Headaches is the essential guide for everyone who suffers from headaches, and will provide the information needed to obtain effective medical care and long-term relief. Different types of headache are thoroughly explained in easy to understand language, beginning with migraine, the most common severe headach.